Live a little : a novel - Jacobson, Howard (Hogarth, 2019)
At the age of ninety-something, Beryl Dusinbery is forgetting everything <U+2013> including her own children. She spends her days stitching morbid samplers and tormenting her two long-suffering carers, Nastya and Euphoria, with tangled stories of her husbands and love affairs. Shimi Carmelli can do up his own buttons, walks without the aid of a frame and speaks without spitting. Among the widows of North London, he<U+2019>s whispered about as the last of the eligible bachelors. Unlike Beryl, he forgets nothing <U+2013> especially not the shame of a childhood incident that has hung over him ever since. There<U+2019>s very little life remaining for either of them, but perhaps just enough to heal some of the hurt inflicted along the way, and find new meaning in what<U+2019>s left. Told with Jacobson<U+2019>s trademark wit and style, Live a Little is equal parts funny, irreverent and tender <U+2013> a novel to make you consider all the paths not taken, and whether you could still change course.